Political Party Financing in Nigeria and Its Implication On Transparency in Governance - Usen, Akpan (PERSPEKTIF, 2024)
Parties financing has been a major challenge in Nigeria since the return of democratic rule in 1999 and currently we are yet to design a process through which political parties should fund their activities as practised globally. .The study examines the implications of parties financing on transparency in governance in Nigerian democratic process. The study contends that illegitimate party financing has brought anti-democratic vices and systemic corruption. The Social Contract theory of Hooker anchored the study. The study utilised both quantitative and qualitative methods of data collection. Data were collected through structured questionnaire and other materials from books, journals, newspapers and inter-net facilities.. The findings reveal that party financing in Nigeria is below global best practice because the sources of funding are not disclosed hence, there is a direct link between party financing and corruption. The institution saddled with responsibility of controlling party’s affair has been relatively weak to interrogate the sources of party finance and as a result undemocratic practices have become prevalent in the system to the detriment of transparency in governance. The study recommends among others that the institution and agencies overseeing party affairs should demonstrate the political will of living above board in order to secure public confidence. The leadership of political parties should be trained on the tradition of transparency and accountability and they should demonstrate proven sense of financial integrity in the management of affairs of fund.